Future applications of host direct therapies for infectious disease treatment - Thom, Ruth E.; D’Elia, R V. (Frontiers in Immunology, 2024)
New and emerging pathogens, such as SARS-CoV2 have highlighted the requirement for threat agnostic therapies. Some antibiotics or antivirals can demonstrate broad-spectrum activity against pathogens in the same family or genus but efficacy can quickly reduce due to their specific mechanism of action and for the ability of the disease causing agent to evolve. This has led to the generation of antimicrobial resistant strains, making infectious diseases more difficult to treat. Alternative approaches therefore need to be considered, which include exploring the utility of Host-Directed Therapies (HDTs). This is a growing area with huge potential but difficulties arise due to the complexity of disease profiles. For example, a HDT given early during infection may not be appropriate or as effective when the disease has become chronic or when a patient is in intensive care. With the growing understanding of immune function a new generation of HDT for the treatment of disease could allow targeting specific pathways to augment or diminish the host response, dependent upon disease profile, and allow for bespoke therapeutic management plans. This review highlights promising and approved HDTs that can manipulate the immune system